2019
DOI: 10.1177/0272431619874400
|View full text |Cite
|
Sign up to set email alerts
|

Associations of Early Adolescents’ Best Friendships, Peer Groups, and Coolness With Overt and Relational Aggression

Abstract: This study examined associations of best friend and peer group aggressive characteristics with students’ overt and relational aggression, and whether coolness moderated these associations across the fall and spring of the first year in middle school. Students ( N = 174; 57% females) self-reported best friendship and peer group members, as well as peer-nominated coolness and aggression (overt, relational). Results indicated positive relations of best friend and peer group aggressive characteristics with subsequ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 77 publications
0
3
1
Order By: Relevance
“…None of these covariates was significant, indicating that participants’ behavior in the task did not depend on their own social status, or smartness nominations. Contrary to what previous studies suggested (Shi & Xie, 2012; Sijtsema & Lindenberg, 2018; Wang et al, 2020), learner social status or perceived achievement did not affect their social information use (Table 3, Model 4). Additionally, including these covariates led to a poorer model fit (higher BIC compared to Model 3).…”
Section: Resultscontrasting
confidence: 99%
See 1 more Smart Citation
“…None of these covariates was significant, indicating that participants’ behavior in the task did not depend on their own social status, or smartness nominations. Contrary to what previous studies suggested (Shi & Xie, 2012; Sijtsema & Lindenberg, 2018; Wang et al, 2020), learner social status or perceived achievement did not affect their social information use (Table 3, Model 4). Additionally, including these covariates led to a poorer model fit (higher BIC compared to Model 3).…”
Section: Resultscontrasting
confidence: 99%
“…Next to the main hypotheses, we conducted an exploratory analysis on whether participants’ own social status and perceived academic achievement influenced their social learning behavior. Since our study was not explicitly designed to address this question, we did not formulate any specific hypothesis for this analysis (but see Sijtsema & Lindenberg, 2018; Wang et al, 2020 for examples of how own social status can be related to social influence). We show that consideration of social relationships in the classroom opens fruitful ways forward in developing novel and potentially more effective forms of peer learning.…”
mentioning
confidence: 99%
“…In educational institutions, learning outcomes are an essential indicator to measure the success of the teaching and learning process (Kashi, 2019;Wang, 2020). Learning outcomes can be said to be maximal if they can provide changes both in knowledge and behavior as a result of interactions (Aikina et al, 2020;Hong, 2021), which are expressed in symbols (Aikina et al, 2020; ?…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, when aggression is normative, students may pay more attention to aggressive acts, which distracts them from learning and makes them attach less value to doing well academically (Thomas et al, 2011 ). A few studies found that aggressive descriptive norms related to lower academic involvement (Wang et al, 2019 ) and that aggressive popularity norms related to lower academic achievement (Dijkstra & Gest, 2015 ). Thus, aggressive descriptive and popularity norms may decrease feelings of belongingness and reduce social, general, and academic self-esteem.…”
Section: Introductionmentioning
confidence: 99%